3D-printed components for quantum devices - Saint, Reece; Evans, William; Zhou, Yijia; Barrett, Thomas J.; Fromhold, T.M.; Saleh, Ehab; Maskery, Ian; Tuck, Christopher; Wildman, Ricky D.; Orucevic, Fedja; Krüger, Peter (Nature Publishing Group, 2018)
Recent advances in the preparation, control and measurement of atomic gases have led to new insights into the quantum world and unprecedented metrological sensitivities, e.g. in measuring gravitational forces and magnetic fields. The full potential of applying such capabilities to areas as diverse as biomedical imaging, non-invasive underground mapping, and GPS-free navigation can only be realised with the scalable production of efficient, robust and portable devices. We introduce additive manufacturing as a production technique of quantum device components with unrivalled design freedom and rapid prototyping. This provides a step change in efficiency, compactness and facilitates systems integration. As a demonstrator we present an ultrahigh vacuum compatible ultracold atom source dissipating less than ten milliwatts of electrical power during field generation to produce large samples of cold rubidium gases. This disruptive technology opens the door to drastically improved integrated structures, which will further reduce size and assembly complexity in scalable series manufacture of bespoke portable quantum devices.